2015
DOI: 10.1590/2237-6089-2014-0036
|View full text |Cite
|
Sign up to set email alerts
|

Managing severe behavioral symptoms of a patient with anti-NMDAR encephalitis: case report and findings in current literature

Abstract: Objective: Psychiatric symptoms emerge in the early stages of anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis, and patients often seek treatment in psychiatric departments before visiting any other general medical services. Numerous articles about anti-NMDAR encephalitis have been published in the scientific community worldwide, but few emphasize the role of psychiatry in symptom management. Case description: We describe the case of a patient with anti--NMDAR encephalitis seen in our service and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another interesting finding of that work was the correlation between violence and organic brain disorders. Other studies report difficulty in managing these patients, 38,39 and the topic deserves further investigation . In our work, the diagnoses of personality disorder were factored into the analysis whenever they were present in the reports.…”
Section: 36mentioning
confidence: 90%
“…Another interesting finding of that work was the correlation between violence and organic brain disorders. Other studies report difficulty in managing these patients, 38,39 and the topic deserves further investigation . In our work, the diagnoses of personality disorder were factored into the analysis whenever they were present in the reports.…”
Section: 36mentioning
confidence: 90%
“…Multiple studies have reported sleep-wake cycle disturbances and insomnia as characteristic symptoms in anti-NMDAR encephalitis [7] and while they have been described previously as the presenting feature in adults [16, 17], insomnia in children with anti-NMDAR encephalitis is typically described later in the clinical course [1, 2629] or has not been mentioned as a feature of the illness [3032]. Other studies suggest that children are more likely to present with predominantly neurologic symptoms (seizures, abnormal movements, and focal neurologic deficits) than with psychiatric symptoms [26].…”
Section: Discussionmentioning
confidence: 99%
“…Caution must be employed with regards to the use of psychotropic medication, as this can complicate the fluctuating clinical picture; for example, benzodiazepines may exacerbate respiratory depression and impaired consciousness. [47][48][49] In addition, there may be an association between use of antipsychotics and neuroleptic malignant syndrome in anti-NMDAR encephalitis. 16 Overall, these risks need to be balanced against the potential benefit of alleviating distressing symptoms and hazardous behaviour.…”
Section: Acute Behavioural Managementmentioning
confidence: 99%